A planning strategy: The Santa Cruz Valley. - Government of the Republic of Trinidad and Tobago. Ministry of Planning and Development. (Town and Country Planning Division., 2011)
Describes the Santa Cruz Valley, its natural resources such as geology and vegetation, its potential for development and problems, and the impact of urbanization on population and the labour force.
Keywords: Development planning - Trinidad and Tobago, Land use - Santa Cruz, Physical planning - Housing developments, Urban planning - Santa Cruz, Demographics - Santa Cruz, Environment - Santa Cruz, Employment - Santa Cruz.